Draft Annual Plan 1976-77 Volume VII Miscellaneous (Statistics, Information, Govt. Presses, Weights and Measures, Ladakh and Backward Areas ) Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1975)
This is a continuing scheme for which staff and other charges have been provided for under the non-plan budget. As the addl. Technical staff proposed under this scheme has not yet been sanctioned, no expenditure has been incurred so far during the current year, However, the provision is expected to be utilized with the sanction of the additional staff on the trials of high yielding varieties of seeds and grass The scheme envisages the development of fodder and dry fruits apricots, almonds, walnuts and grapes.
Government of Jammu and Kashmir, Department of Planning and Development